Optimization of renewable energy utilization in hybrid power systems to achieve sustainable national energy resilience - Pratolo Rahardjo; Dedi Umar (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study examines the optimization of renewable energy utilization in hybrid power generation systems to achieve sustainable national energy security in Indonesia. The research is motivated by increasing energy demand, the depletion of fossil fuel reserves, and commitments to carbon emission reduction. It highlights major challenges in integrating renewable energy into conventional power systems, including limited grid infrastructure, high initial investment costs, the intermittency of sources such as solar and wind, and constraints in energy storage technologies. The study employs a library research approach by analyzing primary and secondary data from scientific books, national and international journal articles, energy agency reports, and case studies of hybrid system implementation in several regions of Indonesia. The findings indicate that Indonesia possesses abundant renewable energy resources—such as solar, wind, hydro, and biomass—which, if effectively integrated into hybrid systems, can enhance electricity supply reliability, reduce dependence on fossil fuels, and strengthen national energy security. The study concludes that developing renewable energy–based hybrid power plants is a key strategy for achieving long-term energy resilience and supporting sustainable development in Indonesia.